2017
DOI: 10.1038/srep40512
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide-mediated interspecific competition between local and invasive thrips pests

Abstract: Competitive interactions between species can be mitigated or even reversed in the presence of anthropogenic influences. The thrips species Frankliniella occidentalis and Thrips tabaci are highly invasive and damaging agricultural pests throughout the world. Where the species co-occur, one species tends to eventually predominate over the other. Avermectin and beta-cypermethrin are commonly used insecticides to manage thrips in China, and laboratory bioassays demonstrated that F. occidentalis is significantly le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…Research also found Thrips tabaci was the dominant species on Brassica oleracea when no insecticide was used but was displaced by F. occidentalis under avermectin and betacypermethrin use (Zhao et al, 2017). Thus, insecticides could be an important factor in intensifying the competition between F. occidentalis and T. tabaci in eastern China (Zhao et al, 2017). In our study, we found that F. occidentalis maintained a higher population density than F. intonsa in three of the sampled host plants in most cases, especially in imidacloprid-used fields.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research also found Thrips tabaci was the dominant species on Brassica oleracea when no insecticide was used but was displaced by F. occidentalis under avermectin and betacypermethrin use (Zhao et al, 2017). Thus, insecticides could be an important factor in intensifying the competition between F. occidentalis and T. tabaci in eastern China (Zhao et al, 2017). In our study, we found that F. occidentalis maintained a higher population density than F. intonsa in three of the sampled host plants in most cases, especially in imidacloprid-used fields.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, F. occidentalis has displaced F. gemina in Argentina on Lycopersicon esculentum (De Piìccolo et al, 2006), and Thrips hawaiiensis has been displaced by F. occidentalis on Rosa chinensis and Gardenia jasminoides, Cao et al (2018). Research also found Thrips tabaci was the dominant species on Brassica oleracea when no insecticide was used but was displaced by F. occidentalis under avermectin and betacypermethrin use (Zhao et al, 2017). Thus, insecticides could be an important factor in intensifying the competition between F. occidentalis and T. tabaci in eastern China (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific competition can be affected by anthropogenic factors such as global warming and farming practice [ 10 , 15 ]. Species displacement by the outcome of interspecific competition, has particular relevance to pest management and conservation biology [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing densities of F. occidentalis lowered the average reproductive success of F. bispinosa females, which may have caused F. occidentalis to be the better competitor (Northfield et al 2011). Nevertheless, competition can be affected by other external factors, such as weather condition and insecticide application, and pesticide-mediated interspecific competition has recently been reported between local and invasive thrips species in China (Zhao et al 2017).…”
Section: Discussionmentioning
confidence: 99%